The impact of copyright law on the digitization of library collections in academic libraries in Malaysia - Tay, Pek San; Lim, Heng Gee; Abdul Ghani Azmi, Ida Madieha; Sik, Cheng Peng (Faculty of Computer Science & Information Technology, University of Malaya, 2017)
The advancements made to digital technology have enabled academic libraries today to digitize their collections as a continuing process of improving their services to the academic community. Various factors determine whether a library should embark on a digitization project and the extent of the digitization. These include the policy of the institution, its financial resources, its manpower, its technical capability and the legality of digitization under the copyright law of each country. The objective of this study is to examine how Malaysian copyright law impacts on the digitization of collections in academic libraries in this country. The focus is on materials which are in the form of literary works as these represent the bulk of most academic libraries’ collections. The study discusses the principles of copyright law that have a direct bearing on digitization, the potential liability of libraries for copyright infringement, the circumstances under which digitization is exempted from copyright infringement and the options available to academic libraries to embark on digitization projects without infringing copyright law. The methodology used is the doctrinal research methodology in the discipline of law. The findings of this study serve to expand the current body of knowledge on how digitization of library collections in academic libraries may be carried out within the confines of copyright law. The recommendations are two-fold. First, academic libraries may digitize materials if the purpose is to cater to the needs of those who are visually or hearing impaired. Secondly, in other cases, digitization may only be carried out after obtaining a licence or an assignment of copyright from the copyright owner. It is hoped that the study would provide librarians with a better understanding of the copyright issues that arise from digitization and the principles of copyright law that govern digitization so that libraries can act within the confines of copyright law.